Power, Protection, and Free Trade International Sources of U.S. Commercial Strategy, 1887-1939 - Lake, David A. (Cornell University Press, 2018)
Why do nations so frequently abandon unrestricted international commerce in favor of trade protectionism? David A. Lake contends that the dominant explanation, interest group theory, does not adequately explain American trade strategy or address the contradictory elements of cooperation and conflict that shape the international economy. Power, Protection, and Free Trade offers an alternative, systemic approach to trade strategy that builds on the interaction between domestic and international factors. In this innovative book, Lake maintains that both protection and free trade are legitimate and effective instruments of national policy, the considered responses of nations to varying international structures.